Якість вихідного коду у зв’язу з підтвердженною технічною заборгованністю - Гринько, А. М. (ХНУРЕ, 2021)
The purpose of this study is to find a connection between code quality issues, found by SonarQube and those marked as SATD. The obtained result demonstrates that the introduction of SATD is usually related to certain types of issues.
Науковий керівник – д.т.н, проф. Смеляков К.С.
Keywords: вихідний код; технічна заборгованість